KINERJA PEGAWAI DALAM PELAYANAN KEPADA NASABAH DI PT. BPR BUMI RIAU INSANI KABUPATEN KAMPAR - Noni Permata Sari; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
A company performance was mirrored by performance employee. But how to gauge the performance employees are doing performance evaluation. Performance evaluation process is an organization in to assess performance that is done by the aim is to give feedback to the employees in efforts to improve display its work and effort to increase productivity organization, and in particular carried out in relation to various wisdom to employees such as for the purpose, the salary increase promotion, education and training and others. The aim of this research is to know their performance PT. BPR Earth Riau Insani Kampar Regency in the service to the customers and to know these factors that support and hamper performance. PT. BPR Bumi Riau Insani Kampar Regency in the service to the customers.Research method uses qualitative research method of research. This research will be done in . BPR Earth Riau Insani Kampar Regency. While in the collection data that is by using interview technique to informers competent in direct observation and field.This research concluded performance in personnel services to customers in rural banks Earth. Kampar Regency in Riau Insani indicators quality of work has been done with good this. BPR Earth Riau Insani Kampar Regency to improve performance employees apply unique culture is one of them to give knowledge and skills to improve employee regularly is 2 times a day in a week so that civil servants to form a number of competencies that one officer that includes loyalty, discipline, cooperation and responsibility to provide excellent service to the customers. While quantity employee work that I see based on financial report that continues to increase every year. And the implementation supervision at PT BPR Kampar Regency, Riau Insani, including work agenda that was established in work culture. BPR Kampar Regency, Riau Insani and teaching at a time when hours before and after services to customers.while performance based on the presence, . BPR Earth Riau Insani Kampar Regency to apply leave for 12 days and the conversion indicators, PT BPR Kampar Regency, Riau Insani provide equipment for each of its work employee who has been determined, if there is a damage there is a part technician who has been appointed BPR Earth Riau Insani. Kampar Regency to fix it. The factors factors that support or hinder performanceBPR Earth Riau Insani. Kampar Regency in the service to the customers based on: the rate of economic growth, development of palm oil plantations Kampar District, the growth in the Micro, Small and Medium Enterprises (MSMEs) in Kampar District, and the leadership .Key words : performance, and his servants, . BPR Earth Riau Insani Kampar Regency